Authorship verification of disputed Hadiths in Sahih al-Bukhari and Muslim. (17th August 2018) - Elewa, Abdelhamid
Abstract: Some argue that some religious books, Prophetic Traditions in particular, are adulterated, but this was sorted out by introducing a manual methodology for identifying authentic and non-authentic texts. The methodology is not precise and has become time-consuming and a daunting process today. A general motivation for many recent studies has been the desire to automate some descriptive processes and employ scientific observation in authorship identification/verification. Using methods of Authorship Verification to examine sensitive texts, like established religious texts, could challenge the existing paradigms in Islamic discourse and any religion that has sacred texts. However, it could lead to the refining of these texts and eliminate any contested belief/s. The selected linguistic features are used to measure the validity of morphological structures (word length), syntactic structure (word type), and lexical richness across the disputed and undisputed Hadiths. Using the three linguistic measures together enabled us to draw each Hadith in a three-dimensional space, with word length plotted along lexical richness and word type. The results for the selected Hadiths that have been measured showed marked differences that could be augmented by examining further features.